2007
DOI: 10.1016/j.febslet.2007.02.053
|View full text |Cite
|
Sign up to set email alerts
|

FurA modulates gene expression of alr3808, a DpsA homologue in Nostoc (Anabaena) sp. PCC7120

Abstract: The DNA-binding protein from stationary phase (Dps) protein family plays an important role in protecting microorganisms from oxidative and nutritional stresses. In silico analysis of the promoter region of alr3808, a dpsA homologue from the cyanobacterium Nostoc sp. PCC7120 shows putative ironboxes with high homology with those recognized by FurA (ferric uptake regulator). Evidence for the modulation of dpsA by FurA was obtained using in vitro and in vivo approaches. SELEX linked to PCR was used to identify P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…In Anabaena sp. PCC 7120, prxA and dpsA contain multiple AT-rich regions that partially match with the FurB (Zur) consensus sequence described previously (Napolitano et al 2012), and are modulated by additional regulatory factors (Hernandez et al 2007;Yingping et al 2014), as also reported in the case of heterotrophic bacteria (Kallifidas et al 2009). …”
Section: Fur and Oxidative Stressmentioning
confidence: 80%
“…In Anabaena sp. PCC 7120, prxA and dpsA contain multiple AT-rich regions that partially match with the FurB (Zur) consensus sequence described previously (Napolitano et al 2012), and are modulated by additional regulatory factors (Hernandez et al 2007;Yingping et al 2014), as also reported in the case of heterotrophic bacteria (Kallifidas et al 2009). …”
Section: Fur and Oxidative Stressmentioning
confidence: 80%
“…However, we failed to detect binding of NtcA to the dpsA UPSR even if this DNA-binding protein is overexpressed under nitrogen starvation. 35,39 Dual recognition of the xisA and hanA UPSRs, whose expression is required at the first stages of heterocyst differentiation, 40,41 was also detected by EMSA. Brusca et al 42 identified a regulatory region upstream xisA that blocks its expression in vegetative cells.…”
Section: Experimental Validation Of Potentially Co-regulated Genesmentioning
confidence: 94%
“…Recent research showed that DpsA (alr3808), a hemecontaining member of Dps family (22), which receives regulation from Ferric Uptake Regulator (FurA) (23), also exists in Anabaena sp. PCC 7120.…”
Section: Discussionmentioning
confidence: 99%